Rainfall Runoff Modelling Using Generalized Neural Network and Radial Basis Network - Gowda, C Chandre; S. G., Mayya (International Journal of Intelligent Systems and Applications in Engineering, 2014)
Rainfall runoff study has a wide scope in water resource management. To provide a reliable prediction model is of paramount importance. Runoff prediction is carried out using generalized regression neural network and radial basis neural network. Daily Rainfall runoff model was developed for Nethravathi river basin located at the west coast of Karnataka, India. The comparative study showed Radial basis neural network performed better than generalized neural network during its evaluation by performance indicators